2015
DOI: 10.1136/bjsports-2015-094869
|View full text |Cite
|
Sign up to set email alerts
|

Doha agreement meeting on terminology and definitions in groin pain in athletes

Abstract: BackgroundHeterogeneous taxonomy of groin injuries in athletes adds confusion to this complicated area.AimThe ‘Doha agreement meeting on terminology and definitions in groin pain in athletes’ was convened to attempt to resolve this problem. Our aim was to agree on a standard terminology, along with accompanying definitions.MethodsA one-day agreement meeting was held on 4 November 2014. Twenty-four international experts from 14 different countries participated. Systematic reviews were performed to give an up-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
378
1
22

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 416 publications
(404 citation statements)
references
References 22 publications
3
378
1
22
Order By: Relevance
“…1 The hip joint is a possible source of symptoms for athletes who complain of anterior hip and groin pain. 2 Hip related groin pain in young athletes is often attributed to Femoroacetabular Impingement Syndrome (FAIS).…”
Section: Introductionmentioning
confidence: 99%
“…1 The hip joint is a possible source of symptoms for athletes who complain of anterior hip and groin pain. 2 Hip related groin pain in young athletes is often attributed to Femoroacetabular Impingement Syndrome (FAIS).…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3,4 In athletes with groin and low back pain, accurate diagnosis and appropriate treatment can be challenging due to complex anatomy and similar clinical patient complaints,. 5,6,7 Musculoskeletal differential diagnosis within the lumbopelvic hip complex includes discernment regarding pathologies that may be intra-articular (i.e. acetabular labral tears, cartilaginous damage) or extra-articular (muscular in nature) to the hip.…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction related to the core and adductor muscle complex and/or the pubic, inguinal, and lumbar regions must also be considered as a potential source of groin pain. 2,7 Further complicating the presentation is the possibility of multiple coexisting diagnoses 3 and regional interdependence as a contributing factor to local pain and impairment, 8 as well as global movement system dysfunction. It has been found that up to 94.1% of athletes diagnosed with athletic pubalgia have radiographic evidence of femoral acetabular impingement (FAI) 9,10,11 while hip and groin pathology and low back pain have been proposed to be found concurrently in the same patient population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] The typical groin injury involves one or more anatomical structures in the groin region. Recent consensus [4] describes categorisation of groin injuries based on the involved clinical entities: adductorrelated, iliopsoas-related, inguinal-related, pubic-related and hip-related groin pain. There is acknowledgement that multiple pathologies can coexist in patients with chronic groin pain, with hip joint pathology thought to be a major contributor to secondary breakdown of adjacent structures.…”
mentioning
confidence: 99%